Profile of estimated glomerular filtration rate of children with Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome - Ezeh, Gabriel O.; Oniyangi, Oluseyi; Babaniyi, Iretiola B.; Nwatah, Vincent E.; Eke, Felicia U. (International Journal of Contemporary Pediatrics, 2019)
Background: Kidney disease is more common in people of African descent in developed countries. Studies reporting estimate Glomerular Filtration Rate (eGFR) in African populations and people living with HIV have been carried more frequently on adults than children. The study aimed to assess eGFR by use of the SCHWARTZ formula in HIV infected children seen at tertiary hospital. Methods: A descriptive, prospective and cross sectional study of 221 children with HIV infection. Schwartz formula was used to determine eGFR. The main outcome measures were eGFR. The study population comprised HIV infected children attending Paediatric out-patients’ clinic and those admitted into the Paediatric wards, aged between 6 months and 15 years. Data was analysed using SPSS version 20 and results presented in tables and figures. Results: The age range of the study subjects was 12 months to 15 years with the mean age and SD of 8.21±3.61 years. There were 129 (58.4%) male and 92 (41.6%) female children with male to female ratio 1: 0.7. The mean age for males was 7.87±3.49 years while that for females was 8.70±3.71 years. The eGFR for the study as determined by Schwartz formula had a range of 49.21 to 463.67 ml/ min/ 1.73m2 with the mean of 159.56±59.04 ml/min. The mean eGFR for the males and females were 166.39±63.54ml/ min and 149.99±45.01 ml/ min respectively. Conclusion: The study, in comparison with other studies, observed a lower prevalence of CKD in HIV infected children. Detection of CKD in HIV infection children may be more optimal if combined methods are employed.